A educação do campo, a luta pela terra e a (re)produção camponesa no município de Goiás-GO - Moreira, Dorcelina Aparecida Militão (2016)
The Rural Education purposes born with the struggle for land, due to the constitutive process of Brazilian society that always neglected rural populations. Perceiving themselves as subjects of rights, rural people begin to fight for the Rural Education within the MST camps, in the 1980s, justified by the everyone rights to access to education and the quality of offered education and must be in accordance with the specificities of the peasantry. In that context, in the city of Goiás, in the countryside there were only multisseriate and destructured schools, aimed only to the first stage of elementary school. Over the years and with the persistence of social movements, intensified the process of struggle for land and also extended to the discussions on the Rural Education, the academic, political and legislative areas. In 2015, there are, in the city of Goiás, 23 Settlement Projects with 722 resettled families fighting for education and the continuity of life in the field. This study aimed to understand the relationship between the Rural Education, the struggle for land and peasant reproduction in the Municipality of Goiás, after 30 years of agrarian reform and identify the main achievements and challenges experienced by the subjects of the field as the main actors of the educational process . In this sense, were made documentary studies, research and observations in-polo schools, located in the countryside, and the Agricolan Family School of Goiás- EFAGO; also sought to know the Teacher Training Course in Rural Education modality offered by the Federal University of Goias. The results showed that, during these 30 years, many achievements have been made and that the existence of schools in the countryside near communities, as well as the Rural Education project are synonymous with peasant resistance. However, there is still much to win, both structural, as in pedagogical issues, if need, thus, families of political articulation for the development of an educational project based on class consciousness, in labor relations and organization and struggle of peasant families, for effective citizenship and the economic, environmental and social sustainability in peasant territory.